Análisis de la temporalidad aristotélica desde la fenomenología de Emmanuel Levinas - Aguirre Jiménez, David José (2023)
This work is a phenomenological reflection about the conception of time in Aristotle from the diachrony of Levinas. The distinction about time in Husserl is taken in order to establish how —in the event of waiting for another (Aristotle)— the indeterminacy of intersubjectivity is manifested. In this way, this confirms that Levinas and Aristotle would have conceptions of time from otherness.